2016
DOI: 10.1097/mnm.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite nanoparticles

Abstract: HApN were synthesized successfully with suitable characteristics for in-vivo applications. Tc-HApN was prepared and showed high stability. Tc-HApN presented increasing bone uptake over time, showing a higher affinity to bone tissues in contrast to surrounding muscle. The present results, together with further studies, may indicate a potential application of HApN as a nanocarrier for bone diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The agglomerates that conform the HA particles may present high rugosity that in turn results in high superficial area values. The specific surface area values found in our study were in the order of the values reported in the literature, which included a wide range from 23.27 m 2 /g [34] to 103.05 m 2 /g [35].…”
Section: Discussionsupporting
confidence: 71%
“…The agglomerates that conform the HA particles may present high rugosity that in turn results in high superficial area values. The specific surface area values found in our study were in the order of the values reported in the literature, which included a wide range from 23.27 m 2 /g [34] to 103.05 m 2 /g [35].…”
Section: Discussionsupporting
confidence: 71%
“…Such low surface charge gives HAP an advantage over the systems that rely on high electrostatic charge, especially if positive, to permeate the plasma membrane and enter the cytoplasm, the reason being the proneness of the latter types of systems to react with the first oppositely charged barriers that they encounter en route to the target tissue while traveling through the vasculature. 35 Although moderate aggregation of nanoparticles in suspension is not ideal, the 300–500 nm hydrodynamic diameter range of HAP/SPION hybrids (Table 3) is adequate for parenteral application, 36 given that this submicron size range is still considerably lower than the 5–10 μ m diameter of the smallest capillary or the dimensions of the discoid erythrocytes: 7 × 1.7 μ m on average. Intravenously administered formulations containing HAP particles with 20–60 μ m in size were used earlier without any adverse effects.…”
Section: Resultsmentioning
confidence: 99%
“…In vivo experiments will be also needed to assess if there are pharmacokinetic benefits of the HAP component compared to the fast clearance and low blood circulation half-life of pure SPIONs: 10 and 90 min for t α 1/2 and t β 1/2 , respectively. 102 Although HAP microparticles did not exhibit any significantly longer pharmacokinetic half-life than SPIONs, their blood residence time was a bit longer, 36 which may be beneficial since the prolonged presence in the bloodstream increases the chances of reaching the tumorous tissue. HAP particles injected intravenously also inhibit platelet aggregation and the coagulation cascade, 103 which is an effect that can indirectly favor tumor targeting via the enhanced permeability and retention (EPR) effect.…”
Section: Discussionmentioning
confidence: 99%
“…Ah igh concentrationw as observedi nl iver and spleen after uptake by macrophages. [124] The intravenous injection of calcium phosphate nanoparticles leads to ap ronouncedd istribution in the body,w ith liver, lung and spleen the most prominentt arget organs. Their longterm fate is unknown, but based on the known cell-biological effects, it can be safely assumed that they will be taken up by cells (including macrophages) and dissolved to the constituting harmlessi ons, that is, Ca 2 + and PO 4 3À ,u nlike other insoluble inorganic and polymeric nanoparticles.…”
Section: Biomedical Applications Of Calcium Phosphate Nanoparticlesmentioning
confidence: 99%